2009
DOI: 10.1073/pnas.0807487106
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of dimeric cardiac L-type calcium channel regulatory domains bridged by Ca 2+ ·calmodulins

Abstract: Voltage-dependent calcium channels (CaV) open in response to changes in membrane potential, but their activity is modulated by Ca 2؉ binding to calmodulin (CaM). Structural studies of this family of channels have focused on CaM bound to the IQ motif; however, the minimal differences between structures cannot adequately describe CaM's role in the regulation of these channels. We report a unique crystal structure of a 77-residue fragment of the Ca V1.2 ␣1 subunit carboxyl terminus, which includes a tandem of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
125
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(135 citation statements)
references
References 27 publications
9
125
0
Order By: Relevance
“…Secondary structures were calculated using Stride (Frishman & Argos, 1995). Solvent accessibility and interface burial were calculated using the GETAREA tool (Fraczkiewicz & Braun, 1998) on the following PDB entries: for UBE2I: 3UIP (Gareau et al , 2012); 4W5V (Boucher et al unpublished); 3KYD (Olsen et al , 2010); 2UYZ (Knipscheer et al , 2007); 4Y1L (Alontaga et al , 2015); for SUMO1: 2G4D (Xu et al , 2006); 2IO2 (Reverter & Lima, 2006); 3KYD (Olsen et al , 2010); 3UIP (Gareau et al , 2012); 2ASQ (Song et al , 2005); 4WJO (Cappadocia et al , 2015); 4WJQ (Cappadocia et al , 2015); 1WYW (Baba et al , 2005); for calmodulin: 3G43 (Fallon  et al , 2009); 4DJC (Sarhan et al , 2012); and for TPK1: 3S4Y (Baker et al , 2001). …”
Section: Methodsmentioning
confidence: 99%
“…Secondary structures were calculated using Stride (Frishman & Argos, 1995). Solvent accessibility and interface burial were calculated using the GETAREA tool (Fraczkiewicz & Braun, 1998) on the following PDB entries: for UBE2I: 3UIP (Gareau et al , 2012); 4W5V (Boucher et al unpublished); 3KYD (Olsen et al , 2010); 2UYZ (Knipscheer et al , 2007); 4Y1L (Alontaga et al , 2015); for SUMO1: 2G4D (Xu et al , 2006); 2IO2 (Reverter & Lima, 2006); 3KYD (Olsen et al , 2010); 3UIP (Gareau et al , 2012); 2ASQ (Song et al , 2005); 4WJO (Cappadocia et al , 2015); 4WJQ (Cappadocia et al , 2015); 1WYW (Baba et al , 2005); for calmodulin: 3G43 (Fallon  et al , 2009); 4DJC (Sarhan et al , 2012); and for TPK1: 3S4Y (Baker et al , 2001). …”
Section: Methodsmentioning
confidence: 99%
“…The CaBP4 mutants M251A, F264E, and L268A showed at least 2-fold weaker binding with a significant loss in binding entropy, consistent with the removal of a hydrophobic interaction for each mutant ( Table 2). The CaBP4 C-lobe bound to the Cav1.4 IQ helix had the same relative orientation as the CaM C-lobe bound to the Cav1.2 IQ helix (49,50) (Fig. 8B).…”
Section: Structure Of Cabp4 and Interaction With Cav14mentioning
confidence: 91%
“…Instead, an experimentally guided computational approach was used to dock the NMR structures of Ca 2ϩ -bound CaBP4 (Fig. 4) onto a modeled helical structure of the Cav1.4 IQ motif, derived from the helical Cav1.2 IQ motif seen in previous crystal structures (49,50). The helical structure of the IQ peptide bound to CaBP4 was confirmed by circular dichroism (Fig.…”
Section: Structure Of Cabp4 and Interaction With Cav14mentioning
confidence: 96%
See 1 more Smart Citation
“…CaM fused protein naturally exists as a kinase in plant 38 and was successfully used for structural study by generating a CaM-MLCK derived peptide (M13) hybrid molecule, as reported by the Ikura's group. 39 Such hybrid proteins have a stoichiometry of 1:1 for CaM fused to the kinase or for CaM and target molecule such as MLCK. The original reason for the construction of the fusion channels was that they could be useful proteins for biochemical or structural studies such as to be used for protein crystallization.…”
Section: Reflections By Tuck Wah Soong Singaporementioning
confidence: 99%